Case Report: Halting terminal osseous overgrowth post tibia amputation in children: a report of three cases - Pon, Chee-Chun; Ong, Ting-Jie; Abd Rasid, Ahmad Fazly; Abd Rashid, Abdul Halim; Jamil, Kamal (Frontiers in Surgery, 2024)
Terminal osseous overgrowth is a common complication after trans-diaphyseal amputation in children, leading to pain, soft tissue problems, and recurrent surgical procedures. We report three different cases with post-amputation issues of osseous overgrowth, ulceration, and deformity over the amputation site. The first case involves a 9-year-old boy with a right leg congenital amputation secondary to amniotic band syndrome. The right below-knee stump later experienced recurrent episodes of osseous overgrowth, leading to ulceration. After the prominent tibia was resected and capped with the ipsilateral proximal fibula, a positive outcome was achieved with no more recurrent overgrowth over the right leg stump. The second case involves a 9-year-old girl born with an amniotic constriction band over both legs. Her left leg remained functional after a circumferential Z-plasty, but the right leg was a congenital below-knee amputation. Multiple refashioning surgeries were performed on the right leg due to osseous overgrowth but the patient continued to experience recurrent overgrowth causing pain and difficulty fitting into a prosthesis.We performed osteocartilaginous transfer of the proximal part of the ipsilateral fibula to the right tibial end, successfully preventing the overgrowth of the tibia without any complications. The third case involves an 11-year-old boy with a history of meningococcal septicemia who underwent a right below-knee amputation and left ankle disarticulation due to complications of septic emboli. He experienced a prominent right distal tibia stump, which later developed into valgus deformity as a result of the previous insult to the proximal tibial growth plate. We performed a corrective osteotomy over the proximal right tibia and capped the entire tibia with the ipsilateral fibula as an intramedullary splint for the osteotomy site. Post-operatively, we achieved satisfactory deformity correction and successfully halted the recurrent overgrowth over the right tibia stump. The method of ipsilateral fibula capping is safe and effective in managing the osseous overgrowth complications in trans-diaphyseal amputations among children.Therefore, it is a reasonable option during primary below-knee amputations in children compared to multiple refashioning surgeries.